The Impact of Intraoperative Donor Blood on Packed Red Blood Cell Transfusion During Deceased Donor Liver Transplantation: A Retrospective Cohort Study. Issue 7 (July 2021) - Shaylor, Ruth; Desmond, Fiona; Lee, Dong-Kyu; Koshy, Anoop Ninan; Hui, Victor; Tang, Gia Toan; Fink, Michael; Weinberg, Laurence
Abstract : Background: Blood from deceased organ donors, also known as donor blood (DB), has the potential to reduce the need for packed red blood cells (PRBCs) during liver transplantation (LT). We hypothesized that DB removed during organ procurement is a viable resource that could reduce the need for PRBCs during LT. Methods: We retrospectively examined data on LT recipients aged over 18 y who underwent a deceased donor LT. The primary aim was to compare the incidence of PRBC transfusion in LT patients who received intraoperative DB (the DB group) to those who did not (the nondonor blood [NDB] group). Results: After a propensity score matching process, 175 patients received DB and 175 did not. The median (first–third quartile) volume of DB transfused was 690.0 mL (500.0–900.0), equivalent to a median of 3.1 units (2.3–4.1). More patients in the NDB group received an intraoperative PRBC transfusion than in the DB group: 74.3% (95% confidence intervals, 67.8-80.8) compared with 60% (95% confidence intervals, 52.7-67.3); P = 0.004. The median number of PRBCs transfused intraoperatively was higher in the NDB group compared with the DB group: 3 units (0–6) compared with 2 units (0–4); P = 0.004. There were no significant differences observed in the secondary outcomes. Conclusions: Use of DB removed during organ procurement and reinfused to the recipient is a viable resource for reducing the requirements for PRBCs during LT. Use of DB minimizes the exposure of the recipient to multiple donor sources. Abstract : Supplemental Digital Content is available in the text.